Histological Changes In The Liver Of The Adult Wistar Rat Following Exposure To Cement Dust (Journal of Biomedical Investigation, 2023)
Background: The Liver regulates many important metabolic functions, and any injury causes distortion of these metabolic functions.Aim: This study investigated the histological changes in the liver of Wistar rats following exposure to cement dust.Methodology: 24 Wistar rats weighing between 250g and 280g were divided into 4 groups of 6 rats per group. Group A rats were placed in a cement dust free environment while Group B-D rats were exposed to various concentration of cement dust dispersed from 5g, 10g and 20g of cement respectively. The weights of the rats were taken weekly and the difference between them and the previous weights were noted. At the end of the 30day exposure, the animals were euthanized under chloroform anaesthesia and the liver was harvested and processed for histological examination. The obtained data analyzed using the paired t-test, with level of significance set at
Keywords: cement dust; liver; histoarchitecture; hepatic disease